2018
DOI: 10.1021/jacs.8b07601
|View full text |Cite
|
Sign up to set email alerts
|

Anti-EGFR Affibodies with Site-Specific Photo-Cross-Linker Incorporation Show Both Directed Target-Specific Photoconjugation and Increased Retention in Tumors

Abstract: A significant challenge for solid tumor treatment is ensuring that a sufficient concentration of therapeutic agent is delivered to the tumor site at doses that can be tolerated by the patient. Biomolecular targeting can bias accumulation in tumors by taking advantage of specific interactions with receptors overexpressed on cancerous cells. However, while antibody-based immunoconjugates show high binding to specific cells, their low dissociation constants ( K) and large Stokes radii hinder their ability to pene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 31 publications
1
18
1
Order By: Relevance
“…After 6 h, ERK activity was reduced by 30% in cells crosslinked to N23BP (Figure 4b) when compared with the untreated control, which correlated well with the cell growth inhibition data shown in Figure 1. For samples treated with uncrosslinkable proteins, an initial reduction in ERK was observed that reversed within 5 h. We hypothesize that the initial reduction in ERK in these samples was caused by the strong binding of these biomolecules to EGFR (WT: 7 nM, N23BP: 22 nM and Cetuximab: 0.4 nM) (Brasino et al, 2018;García-foncillas et al, 2019). Notably, at earlier timepoints the stronger-binding Cetuximab appeared to block ERK activity more effectively than the more weakly-binding WT and N23BP.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…After 6 h, ERK activity was reduced by 30% in cells crosslinked to N23BP (Figure 4b) when compared with the untreated control, which correlated well with the cell growth inhibition data shown in Figure 1. For samples treated with uncrosslinkable proteins, an initial reduction in ERK was observed that reversed within 5 h. We hypothesize that the initial reduction in ERK in these samples was caused by the strong binding of these biomolecules to EGFR (WT: 7 nM, N23BP: 22 nM and Cetuximab: 0.4 nM) (Brasino et al, 2018;García-foncillas et al, 2019). Notably, at earlier timepoints the stronger-binding Cetuximab appeared to block ERK activity more effectively than the more weakly-binding WT and N23BP.…”
Section: Resultsmentioning
confidence: 90%
“…The photo-cross-linkable affibody N23BP was synthesized as explained in Brasino et al (2018). Briefly, an EGFR binding WT affibody Z EGFR:1907 in a pET21b+ vector with a 6XHis Tag at the C-terminus, was procured from Integrated DNA Technologies (IDT) which was then modified to contain a cysteine using a Q5 site-directed mutagenesis kit (New England Biolabs [NEB]), leading to the construction of the N23C plasmid.…”
Section: Expression Synthesis and Purification Of Benzophenone Conjugated Affibodymentioning
confidence: 99%
See 2 more Smart Citations
“… 14 In the second one, RTK is activated optochemically using semi-genetically encoded RTK chimeras in which dimerization or conformational changes are put under the control of photocaged small molecules. 15 , 16 Other optochemical techniques include photocaging of amino acid residues in the kinase domain 17 and photocaging of RTK activators like DNA aptamers, 7 RTK inhibition with light-activatable anti-RTK antibodies (photobodies) 18 , 19 and RTK degradation with an opto-PROTAC (proteolysis targeting chimera) technique. 20 …”
Section: Introductionmentioning
confidence: 99%